(3fSH GdfHj hBd HjJg GdCWgGQs - (3GdHQhLQOj, eMeO Hf YHO GdcQje, cGf MjG (B1122 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3CYde CQTOc Gddg JYGdi Edi WQjb GdMb Cfg dG HO aj ceGd GdeYQaI HMGd GdfHj Udi Gddg Ydjg hYdi idg hGdChUjGA ef HYOg Ydjge GdSdGe eYQaI CfSGHge hehGdjOge hJhGQjN hajGJges
(3BNQgG (B:s
(3BNQgG(B: (3hgh eSJNa HCeQI (B... (3HEXgGQ Gdfhe aj LedI GdfjGe bGe Zdjg aVQHg Ydi Ce QGSg HGdSja hcGfg eSehkeG aecK JSYI YTQ hdjdI GdYTQjf hjhegG hdjdI EMOi hYTQjf Edis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B3: 120 - 121s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs